PRODUKTIVITAS KLON KARET PADA BERBAGAI KONDISI LINGKUNGAN DI PERKEBUNAN - Aidi Daslin (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
Planting of superior clones in plantations have a significant impact in improving productivity. Some clones could show optimal yield when planted in a certain environments but have low productivity in other environments. Indonesia has a wide diversity of environments in order requiring suitable clones for a certain environment. The study was conducted to determine the productivity of some clones in three different environmental conditions on the plantation, which consists of five conventional rubber clones (GT 1, AVROS 2037, RRIM 600, PB 235, PB 260) were planted 1990, six clones of IRR 100 series (IRR 100, IRR 108, IRR 110, IRR 111, IRR 112, IRR 118), and six clones of IRR 200 series IRR (IRR 207, IRR 208, IRR 209, IRR 211, IRR 216, IRR 220) were planted 2004 respectively. The trials were arranged in a randomized block three replication, planting distance of 3.0 x 6.5 m and each plot of 600 trees (12 rows x 50 trees). Observation of latex yield measured in dry rubber productivity (tonnes/hectare). The result showed, there are the differences of clonal response at three locations with different environments in the plantation. The clones of PB 235 and PB 260 have the highest productivity and suitable for the environment I (the low rain fall areas) with yield per hectare cumulative of fifteen tapping years are 30.1 and 29.2 tonnes respectively. Clone IRR 112 had the best cumulative productivity over five tapping years of 8.4 to 9.2 tonnes/hectare and IRR 118 of 7.2-7.6 tonnes/hectare suitable for the environment I and II and IRR 110 had the highest productivity are 8.0 tonnes/hectares is suitable for environment II (optimal condition). Clones IRR 208 and IRR 211 provide the best yield (7.0 to 7.8 tonnes) and suitable for environment I and II, while clones of IRR 209, IRR 216 and IRR 220 is suitable for environment III (high rain fall areas) with productivity 8.0 to 8.5 tonnes. Development of these clones in appropriate planting environment, will increase the productivity of rubber plantations and agribusiness profits.Keywords : Hevea brasiliensis, rubber, productivity, environment, superior clones